Caregiving Centenarians: Cross-national Comparison in Caregiver-Burden between the United States and Japan - Cho, J. (Aging Ment Health, 2018)
BACKGROUND AND OBJECTIVES. The personal distress associated with caring for a family member has been well documented; however, questions about the burden of caregiving for centenarians and cross-national differences in the caregiving context, remain unanswered. RESEARCH DESIGN AND METHODS. This study includes reports by caregivers of 538 near-centenarians and centenarians in the U.S. and Japan: 234 from the Georgia Centenarian Study and 304 from the Tokyo Centenarian Study. Basic descriptive and multivariate regression analyses were conducted. Mean levels of caregiver burden and near-centenarian and centenarians’ characteristics (as predictors) for caregiver burden were compared between the U.S. and Japan. The near-centenarian and centenarians’ functional capacity and personality were assessed as predictors. RESULTS. Differential predictive patterns in caregiver burden were found in the two groups. In the U.S., near-centenarian and centenarians’ agreeableness and conscientiousness were negatively associated with caregiver burden; whereas the near-centenarian and centenarians’ neuroticism and number of diseases were positively associated with caregiver burden. In Japan, the near-centenarian and centenarians’ activities of daily living, openness, and agreeableness were negatively associated with caregiving burden. Interaction effects between functional capacity and personality, on caregiver burden were observed only in the U.S. In the U.S., higher levels of agreeableness and openness significantly changed the level of caregiver burden associated with vision problems and a greater number of diseases. DISCUSSION AND IMPLICATIONS. Cross-national comparative predictors of caregiving burden between the two countries emphasized that caring for centenarians should be understood in the caregiving context, as well as the social context in the caregiving context.